Resonant aluminum nanodisk array for enhanced tunable broadband light trapping in ultrathin bulk heterojunction organic photovoltaic devices - Wu, Bo (2012)
A cost-effective approach to enhancing broadband light trapping in ultrathin bulk heterojunction organic photovoltaic (OPV) devices is proposed. This is achieved by simply inserting an array of Al nanodisks at the interface of the ITO anode and the organic active layer; forming circular plasmonic nanopatch cavities (between the nanodisks and the Al cathode) that sandwich the active layer. Through interactions between the surface plasmon polaritons localized at the nanodisk and the cathode, a tunable broadband resonance peak spanning 450–700 nm in the scattering cross-section spectrum is formed, thereby enhancing the electromagnetic field in the active layer. Compared to an OPV device with a 60-nm-thick PCPDTBT/PC60BM layer, our numerical simulations reveal that integrated absorption enhancements of up to 40 % can be achieved in an equivalent device integrated with an array of nanodisks with a diameter of 100 nm and a periodicity of 250 nm. From the analysis of the structure–performance relationships, implications for the design of these nanopatch cavities for light harvesting in ultrathin OPV devices are discussed.